2010
DOI: 10.1002/eco.159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure, scrub position, and soil surface components on the hydrological response in small plots in southern Spain

Abstract: Rangelands are a major component of the Mediterranean landscape. These environments are commonly affected by grazing, which reduces vegetation cover. Consequently, patchy vegetation patterns occur on Mediterranean hillslopes, where the bare soil is characterized by a number of surface components that are controlled by climatic conditions and exposure. The aim of this study was to assess at a fine scale the effects of exposure, scrub, and soil surface components on the hydrological response under various Medite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Areas between shrubs in HU and SM were nearly completely uncovered, but not in DY where those areas were mostly covered by annual vegetation from December to June because of a lower pressure of grazing. In fact, the presence of this type of vegetation played a key role in retaining soil particles despite the generation of overland flow (Martínez‐Murillo & Ruiz‐Sinoga, ; Ruiz‐Sinoga et al, ; Gabarrón‐Galeote et al, ), and the sediment concentration registered in DY were almost negligible in many rainfall events that generated overland flow. Another important factor related to vegetation to explain our results were the relative position of vegetation within the plots.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Areas between shrubs in HU and SM were nearly completely uncovered, but not in DY where those areas were mostly covered by annual vegetation from December to June because of a lower pressure of grazing. In fact, the presence of this type of vegetation played a key role in retaining soil particles despite the generation of overland flow (Martínez‐Murillo & Ruiz‐Sinoga, ; Ruiz‐Sinoga et al, ; Gabarrón‐Galeote et al, ), and the sediment concentration registered in DY were almost negligible in many rainfall events that generated overland flow. Another important factor related to vegetation to explain our results were the relative position of vegetation within the plots.…”
Section: Discussionmentioning
confidence: 89%
“…As the climate becomes less rainy, the patchy vegetation pattern becomes more frequent, and the bare soil areas along hillslopes can be easily connected whether the magnitude and intensity of rainfall exceed a certain threshold (Bull & Kirkby, 2002; Cammeraat, ; Ruiz‐Sinoga et al, ; Ruiz‐Sinoga et al, ). The interaction between topography and processes occurring within catchments is key to understanding dynamics of hydrological connectivity (Bracken & Croke, ; Turnbull et al, ; Wainwright et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Under the soil conditions of the study, the microenvironments on the north‐facing hillslope showed a more uniform response from a hydrological point of view than those observed on the south‐facing hillslope. This may be related with the threshold climatic conditions previously reported for the experimental area by other authors (Ruiz‐Sinoga and Martínez‐Murillo, ); (Ruiz‐Sinoga et al ., ; Ruiz‐Sinoga et al ., ). According to Lavee et al ., (), these areas are located in a range from 450 to 700 mm year –1 within the Mediterranean zone, and slight disturbances can trigger degradation feedback processes leading to desertification.…”
Section: Discussionmentioning
confidence: 97%
“…The study of spatial patterns of soil surface components (vegetation, rock fragment cover, rock outcrops, bare soil, litter and soil surface crust) is a key issue for understanding hydrological behaviour in the Mediterranean climate zone because each component differentially influences the soil infiltration capacity, which is the most important runoff controlling factor (Lavee and Poesen, ; Calvo et al ., ; Boix‐Fayos et al ., ; Arnau‐Rosalén et al ., ). The type and dominance of one or several soil surface components is determined by factors including climate, hillslope exposure, topographical position and land use (Poesen and Lavee, ; Kutiel et al ., ; Ruiz‐Sinoga et al ., ). Ruiz‐Sinoga and Martínez‐Murillo, () observed that under Mediterranean conditions soil surface components have highly variable effects on soil hydrological behaviour in both space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a trend of developing and testing physically-based soil erosion models appears [7][8][9][10][11]. In our study, a slope model is constructed in a flume device made of Plexiglas ( Figure 1).…”
Section: Physical Models Monitoring Devices and Experimental Procedmentioning
confidence: 99%